2014
DOI: 10.1016/j.ymeth.2014.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Assays to monitor autophagy in Drosophila

Abstract: The term autophagy refers to the engulfment and degradation of cytoplasmic components within the lysosome. This process can benefit cells and organisms by removing damaged, superfluous, or harmful cellular components, and by generating a supply of recycled macromolecules that can support biosynthesis or energy production. Recent interest in autophagy has been driven by its potential role in several disease-related phenomena including neurodegeneration, cancer, immunity and aging. Drosophila provides a valuable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
159
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(166 citation statements)
references
References 46 publications
5
159
0
2
Order By: Relevance
“…Vesicles labeled with these markers showed almost no overlap in Rab14-depleted cells, with a correlation coefficient similar to the effects of Klp98A depletion ( Figs 3B, 5E,F). We further examined autophagosome-lysosome fusion in Rab14-depleted cells using the acidic compartment dye LysoTracker Red, which in fat body cells specifically labels autophagy-induced acidic vesicles (Mauvezin et al, 2014;Scott et al, 2004). Consistent with a defect in autolysosome formation, strong punctate LysoTracker Red labeling was observed in starved control cells but not in Rab14-depleted cells (Fig.…”
Section: Rab14 Binds To Klp98a and Participates In Autophagosome Matumentioning
confidence: 71%
See 1 more Smart Citation
“…Vesicles labeled with these markers showed almost no overlap in Rab14-depleted cells, with a correlation coefficient similar to the effects of Klp98A depletion ( Figs 3B, 5E,F). We further examined autophagosome-lysosome fusion in Rab14-depleted cells using the acidic compartment dye LysoTracker Red, which in fat body cells specifically labels autophagy-induced acidic vesicles (Mauvezin et al, 2014;Scott et al, 2004). Consistent with a defect in autolysosome formation, strong punctate LysoTracker Red labeling was observed in starved control cells but not in Rab14-depleted cells (Fig.…”
Section: Rab14 Binds To Klp98a and Participates In Autophagosome Matumentioning
confidence: 71%
“…1A). To study the function of Klp98A in autophagy, we examined the effects of Klp98A loss-and gain-of-function on mCherry-tagged Atg8a protein (mCh-Atg8a), a well-characterized marker of autophagosomes and autolysosomes (Klionsky et al, 2012;Mauvezin et al, 2014). Klp98A depletion in fat body cells led to a reduction in the overall number of vesicles marked by mCh-Atg8a, and to their redistribution towards the perinuclear region of the cell ( Fig.…”
Section: Klp98a Depletion Affects Autophagic Vesicle Number and Intramentioning
confidence: 99%
“…S3B). Finally, we turned to a well-characterized physiological setting for TORC1 modulation, specifically starvation-induced inactivation of TORC1 in fly salivary glands cells (Mauvezin et al, 2014). In this background, we also detected a shift of Mitf to the nucleus (supplementary material Fig.…”
Section: Mitf-myc In Vivomentioning
confidence: 92%
“…We found that Klp98A gain-or loss-of-function modified the localization of vesicles marked by the autophagosomal membrane protein Atg8/LC3 and of lysosomes marked by LAMP1. 13 Klp98A depletion significantly disrupted the localization of the 3 populations of vesicles involved in autophagy, i.e., autophagosomes, lysosomes, and autolysosomes. Each of these vesicles was aberrantly localized to the perinuclear area upon Klp98A depletion, and to the cortical region of cells overexpressing Klp98A.…”
mentioning
confidence: 95%